Umur Beranak Pertama terhadap Produktivitas Sapi Perah Periode Laktasi Pertama dan Selang Beranak Pertama - Murdani, K.; Purwanto, B. P.; Atabany, A. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
Dairy cattle productive period is the best time to earned income. This is strongly influenced by the age factor of the first calving and the milk yield production. Based on that, this research conducted to analyze the differences effect of the age of first calving and calving interval on lactation period. The performance of the productivity period dairy cattle to the age of the first calving, calving interval, the empty period, the dry period and the milk yield. This research uses recorded production data from Dairy Cattle Breeding Center (BPT-SP and HMT) Cikole. The data consists of 42 productive dairy cows during the 2011-2017 maintenance period. The data were grouped by age of first calving K1: age of first calving 22-25 months; K2: age of first calving 26-29 months; K3: age of first calving 30-33 months; K4: age of first calving 34-37 months. The results showed that grouping of the first age calving was significanly in each group K1, K2, K3 and K4. The was significanly effect also exists on total milk production of first and second lactation periods in K1 and K2 more than K3 and K4.The results of the analysis the first calving relationship with the production of first and second lactation decreased milk yield production during the lactation period.